Time Course and Role of Exercise-Induced Cytokines in Muscle Damage and Repair After a Marathon Race - de Sousa, Cesar Augustus Zocoler; Sierra, Ana Paula Renno; Martínez Galán, Bryan Steve; Maciel, Jaqueline Fernanda de Sousa; Manoel, Richelieau; Barbeiro, Hermes Vieira; Souza, Heraldo Possolo de; Cury-Boaventura, Maria Fernanda (Frontiers in Physiology, 2021)
Endurance exercise induces an increase in the expression of exercise-induced peptides that participate in the repair and regeneration of skeletal muscles. The aim of the present study was to evaluate the time course and role of exercise-induced cytokines in muscle damage and repair after a marathon race. Fifty-seven Brazilian male amateur marathon finishers, aged 30 to 55 years, participated in this study. Blood samples were collected 24 h before, immediately after, and 24 h and 72 h after the São Paulo International Marathon. Leukogram and muscle damage markers were analyzed using routine automated methodology in the clinical laboratory. Plasma levels of exercise-induced cytokines were determined using the Human Magnetic Bead Panel or enzyme-linked immunosorbent assays [decorin and growth differentiation factor 15 (GDF-15)]. Muscle damage was characterized by an increase in plasma myocellular proteins and immune changes (leukocytosis and neutrophilia). Running the marathon increased interleukin (IL)-6 (4-fold), IL-8 (1.5-fold), monocyte chemoattractant protein-1 (2.4-fold), TNF-alpha (1.5-fold), IL-10 (11-fold), decorin (1.9-fold), GDF-15 (1.8-fold), brain-derived neurotrophic factor (BDNF) (2.7-fold), follistatin (2-fold), and fibroblast growth factor (FGF-21) (3.4-fold) plasma levels. We also observed a reduction in musclin, myostatin, IL-15 and apelin levels immediately after the race (by 22–36%), 24 h (by 26-52%) and 72 h after the race (by 25-53%). Changes in BDNF levels were negatively correlated with variations in troponin levels (r=-0.36). Variations in IL-6 concentrations were correlated with changes in follistatin (r=0.33) and FGF-21 (r=0.31) levels after race and with myostatin and irisin levels 72 h after the race. Changes in IL-8 and IL-10 levels had positive correlation with variation in musclin (p<0.05). Regeneration of exercise-induced muscle damage involves the participation of classical inflammatory mediators, as well as GDF-15, BDNF, follistatin, decorin, and FGF-21, whose functions include myogenesis, mytophagia, satellite cell activation, and downregulation of protein degradation. The skeletal muscle damage markers were not associated to myokines response. However, BDNF had a negative correlation with a myocardial damage marker. Classical anti-inflammatory mediators (IL-10, IL-8 and IL-6) induced by exercise are associated to myokines response immediately after the race and in the recovery period and may affect the dynamics of muscle tissue repair.